Edwardsiella piscicida employs C3 derivative to mediate internalization and infection via the teleost-specific receptor - Mo-Fei Li; Xiao-Yan Jin; Heng Liu; Zhe Feng; Meng Wu; Hong-Qiang Zhang; Yu-Ting Du; Yuan-Yuan Sun; Xue-Peng Li; Jin-Sheng Sun (Virulence)
Edwardsiella piscicida is a prominent fish pathogen, and spreads the infection to humans and mammals. It can resist serum killing and invade the host phagocytic cells. However, the precise mechanisms underlying E. piscicida infection remain unclear. In this study, we found that E. piscicida could bind to complement factor H and recruit complement factor I from Paralichthys olivaceus (Po) serum, leading to the degradation of complement recognition molecule PoC3b to PoC3dg on the bacterial surface. E. piscicida also bound to peripheral blood leukocytes, depending on the teleost-specific interaction between PoC3dg and the integrin beta VWA (INB) domain of PoCD18, whereby facilitating bacterial internalization and infection. When PoCD18 was knocked down or blocked, bacterial infection and tissue lesions were significantly decreased. Mechanistically, the intracellular domain of PoCD18 subsequently interacted with PoCytohesin and triggered the phosphorylation of the phosphatidylinositol 3-kinase (PI3K)/serine-threonine protein kinase (Akt) signalling pathway. Furthermore, inhibition of the PI3K/Akt pathway impaired the internalization and pathogenicity of E. piscicida. Overall, we demonstrated for the first time that E. piscicida utilized the C3dg-CD18 axis to facilitate internalization, thereby targeting immune evasion and promoting systemic infections. These results provide new insights into the pathogen–host interaction mechanism and a potential target to control edwardsiellosis.